Secondary Raised Intracranial Pressure After Cranial Vault Remodeling for Isolated Sagittal Craniosynostosis. Issue 8 (November 2021) - Moore, Mark H.; Chaisrisawadisuk, Sarut; Prasad, Vani; Santoreneos, Stephen; Molloy, Cindy J.
Abstract : Abstract: The management of sagittal craniosynostosis has evolved over the decades as teams seek to refine their surgical approaches to idealize head shape with the least possible morbidity. Here, the authors identify the incidence of raised intracranial pressure (ICP) and its risk factors, requiring secondary surgical intervention after cranial vault remodeling (CVR) procedure at a single tertiary referral craniofacial unit. A retrospective case-control study was performed on the patients with isolated non-syndromic sagittal craniosynostosis. All patients who underwent CVR in our unit and had a minimum of 1.5 years follow-up were included. One hundred and eighty-four patients (134 male and 50 female) who underwent primary CVR surgery for isolated sagittal craniosynostosis were included. Thirteen patients (7.07%) had clinical evidence of late raised ICP resulting in repeat CVR procedures. Higher incidence of raised ICP in patients who had primary surgery before 6 months than after or at 6 months of age ( P  = 0.001). There were 23.5%, 5.6%, 3.2%, and 1.9% of secondary raised ICP patients who underwent the primary surgery between 1999–2004, 2005–2010, 2011–2015 and 2016–2018, respectively ( P  = 0.024). The risk of secondary raised ICP was higher in patients with isolated sagittal craniosynostosis whose primary surgery occurred before the age of 6 months (two times more likely). More extensive CVR can be performed safely in sagittal synostosis with promising outcomes. The late presentation with raised ICP reinforces the importance of long-term multidisciplinary protocol-based follow-up. Abstract : Supplemental Digital Content is available in the text